Engagement and Stance in Academic Writing: A Study of English and Persian Research Articles - Taki, Saeed; Jafarpour, Fatemeh (Richtmann Publishing, 2012)
Written texts of any kind embody some interactions between writers and their potential readers. This study focused onacademic writing to find about linguistic features used by writers to create such interactions. Following Hyland’s (2005) model ofinteraction in which stance and engagement are introduced as two discoursal features having an effective role in constructingwriter-reader interactions, this study aimed at investigating the ways in which English and Persian academics express theirposition to discover the strategies used to bring readers to their writing. To this end, 120 English and Persian research articles intwo disciplines of Chemistry and Sociology were analyzed for the purposes of cross-linguistic and cross-disciplinary comparison.The results demonstrated that the writers of both disciplines, especially the sociologists, considered the expression of stanceand engagement markers in their writing important. However, in sociology articles there was a greater effort to interact withreaders. Further, in Persian there seemed to be more cases of readers’ involvement.